2022
DOI: 10.33862/citradelima.v6i2.336
|View full text |Cite
|
Sign up to set email alerts
|

Spiritualitas dan Religiusitas Pada Pasien Kanker

Abstract: Spirituality is something that is very important to be realized in the health service setting and has a positive impact on cancer patients, especially in the lives of cancer patients themselves. Spirituality can reduce depressive symptoms and improve quality of life in cancer patients. A phenomenon that is still happening today is that many health services only focus on physical problems without paying attention to the psychological and spiritual problems of their patients. So that data on spirituality and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Based on the statement above, previous research was found which stated that religiosity has a significant relationship with self-compassion (Tahmasebi 2018). Research conducted by Wiksuari (2023) on breast cancer patients who are all Muslim states that patients use the power of faith in God and sincerity as acceptance in the diagnosis of breast cancer. And the patient accepts all the deficiencies that occur based on religiosity because it is a gift from God.…”
Section: Relationship Religiosity and Self-compassion In Post-mastect...mentioning
confidence: 99%
“…Based on the statement above, previous research was found which stated that religiosity has a significant relationship with self-compassion (Tahmasebi 2018). Research conducted by Wiksuari (2023) on breast cancer patients who are all Muslim states that patients use the power of faith in God and sincerity as acceptance in the diagnosis of breast cancer. And the patient accepts all the deficiencies that occur based on religiosity because it is a gift from God.…”
Section: Relationship Religiosity and Self-compassion In Post-mastect...mentioning
confidence: 99%
“…These aspects will affect the quality of life of cancer patients. Health services really need to provide spiritual services as the most important part of holistic services so that they do not only focus on the physical, psychological, and social (Wiksuarini et al, 2022)…”
Section: Introductionmentioning
confidence: 99%